Risk assessment for breast cancer and BRCA mutations in women with personal and familial history - doi: 10.4025/actascihealthsci.v35i2.12134 - Clementino, Leandro da Silva; Suzuki, Edinei Hideki; Oliveira, Karen Brajão (Acta Scientiarum. Health Sciences, 2013)
Risk estimation tools can be used in clinical practice to promote the counseling, prevention, or increase the surveillance against breast cancer development. The present study aimed to estimate the risk for breast cancer and the odds for BRCA1/2 mutations, and to correlate the values found by the different models. Breast cancer risk was determined by the models of Gail, Claus, BRCAPRO and Boadicea; and for the mutations, Myriad II, Penn II BRCAPRO, and Boadicea models were utilized, in women who have or had the disease (n = 16) and their respective first degree female relatives unaffected (n = 25). Considering non affected women 16% were categorized as high risk for breast cancer development in five years by the Gail model, and all values presented significant correlation among the models (p < 0.05). Among the participants, 12% (5/41) were considered high risk for BRCA mutations. All the models presented significant correlation between the odds of BRCA1/2 mutation risk, except between Myriad II and Boadicea models. Since there is no model that includes all the variables influencing the development of this disease, it is essential to estimate the risk by more than one model before initiating any clinical intervention.